The pivotal role of sharia supervisory boards in enhancing ESG performance: A maqasid al-shariah perspective - Muhammad, Rifqi; Tumewang, Yunice Karina; Aisyah, Maulidyati; Riantika, Reny Lia; Koeswandana, Noorfaiz Athallah (Proceeding International Conference on Accounting and Finance, 2026)
This conceptual paper examines the critical role of Sharia Supervisory Boards (SSBs) in driving Environmental, Social, and Governance (ESG) performance within Islamic banking institutions. Grounded in Maqāṣid al-Sharī’ah framework and legitimacy theory, we propose that SSBs serve as strategic catalysts rather than mere compliance mechanisms in sustainability transformation. The study introduces novel mediating variables including Spiritual-Ecological Intelligence - the integration of environmental consciousness within Islamic spiritual values, and Maqasid-Based Strategic Alignment - the systematic integration of higher Shariah objectives into corporate strategy. Through synthesis of contemporary literature from Scopus-indexed journals, we develop a comprehensive framework demonstrating how SSB characteristics - particularly diversity, expertise in sustainability matters, and independent oversight - directly influence green financial innovation and stakeholder engagement quality. The paper argues that effective SSBs transcend traditional supervisory functions by fostering Ethical Transformation Mechanisms that align banking operations with both Islamic principles and global sustainability standards. Our conceptual model provides valuable insights for regulators in developing SSB competency frameworks that emphasize sustainability expertise, while offering practical guidance for Islamic banks to leverage their governance structure as competitive advantage in emerging green finance markets. The study contributes to theoretical advancement by bridging Islamic governance principles with contemporary sustainability discourse, proposing testable propositions for future empirical research in Islamic finance and ESG performance literature.